The Role of Tenascin-C in Tissue Injury and Repair After Stroke - Okada, Takeshi; Suzuki, Hidenori (Frontiers in Immunology, 2021)
Stroke is still one of the most common causes for mortality and morbidity worldwide. Following acute stroke onset, biochemical and cellular changes induce further brain injury such as neuroinflammation, cell death, and blood-brain barrier disruption. Matricellular proteins are non-structural proteins induced by many stimuli and tissue damage including stroke induction, while its levels are generally low in a normal physiological condition in adult tissues. Currently, a matricellular protein tenascin-C (TNC) is considered to be an important inducer to promote neuroinflammatory cascades and the resultant pathology in stroke. TNC is upregulated in cerebral arteries and brain tissues including astrocytes, neurons, and brain capillary endothelial cells following subarachnoid hemorrhage (SAH). TNC may be involved in blood-brain barrier disruption, neuronal apoptosis, and cerebral vasospasm via the activation of mitogen-activated protein kinases and nuclear factor-kappa B following SAH. In addition, Post-SAH TNC levels in cerebrospinal fluid predicted the development of delayed cerebral ischemia and angiographic vasospasm in clinical settings. On the other hand, TNC is reported to promote fibrosis and exert repair effects for an experimental aneurysm via macrophages-induced migration and proliferation of smooth muscle cells. The authors review TNC-induced inflammatory signal cascades and the relationships with other matricellular proteins in stroke-related pathology.